PRIMARY SUPRARENAL GLANDULAR TUBERCULOSIS MIMICKING A MALIGNANT TUMOR (Indonesian Journal of Urology, 2023)
ABSTRAK Objective: Our case demonstrates effective tuberculosis-related Addison's disease care with laparoscopic adrenalectomy and anti-tuberculosis medication. Case(s) Presentation: A 43-year-old patient complained of left flank pain for two months before admission, unexplained weight loss, general weakness, decreased appetite, and without long-term cough. The physical examination resulted in hyperpigmentation on the fingers of both hands. MRI revealed an enlarged left adrenal gland and the blood test showed elevated cortisol to 1668 mmol/L. Three-port left laparoscopic transperitoneal adrenalectomy was used. Histopathology results showed epitheloid histiocytes that formed granulomas with caseous necrosis and Datia Langerhans cells referring to tuberculosis; no malignancy was found from the same sample. Discussion: Addison's illness is the primary cause of tuberculosis. Due to the widespread use of anti-TB medications, the incidence of adrenal tuberculosis has been on the decline recently; nonetheless, in developing nations, tuberculosis is still the predominant cause of Addison's disease. Conclusion: Surgery and standard treatment for extrapulmonary tuberculosis were adequate to diagnose and alleviate the symptoms of cortisol disturbance caused by Addison’s disease. Keywords: Endocrine glands, adrenalectomy, tuberculosis endocrine.